Akurasi Jadwal Salat Masjid Baitussalam Gampong Nga Lb Arakeumudi Kecamatan Lhoksukon - Marzhatillah Marzhatillah; Hasna Tuddar Putri (Astroislamica: Journal of Islamic Astronomy, 2022)
The prayer schedule used at the Baitussalam Mosque is the prayer schedule of all time compiled by Abu Muhammad Isa, an astronomer at the time. This prayer schedule is still used and guided by the community. To make it easier for implementation, the mosque management has also provided digital prayer schedule. But unfortunately, even though these facilities have been completed, it's still can cause confusion for the congregation, which schedule is correct to use. Because the schedule that runs automatically on the digital clock is not according to the schedule stated in the prayer schedule of all times. Therefore It is necessary to analyze the method of determining the prayer schedule at the Baitussalam Mosque, Gampong Nga LB Arakemudi, Lhoksukon District and the accuracy of the prayer schedule. This research belongs to the type of qualitative research. The primary data sources in this study are prayer schedules on the all-time prayer schedule and digital clock schedules. The results of this study are the method used in preparing the prayer schedule for the Baitussalam mosque, Gampong Nga LB Arakemudi, Lhoksukon based on the method of calculating the prayer schedule of all times, which uses the classical method in the sense that the input data calculation is still static while the digital prayer schedule uses dynamic data. This is what causes the Baitussalam mosque prayer schedule in Gampong Nga LB Arakemudi, Lhoksukon, between the all-time prayer schedule and the digital prayer schedule, there are varying differences. The several of differences found, some exceeded the limit and some did not exceed the ihtiyat limit, which is 2-3 minutes from the standard prayer times compiled by the Ministry of Religion.